1996
DOI: 10.1073/pnas.93.24.14182
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the growth-associated protein GAP-43 are selectively increased in association cortices in schizophrenia

Abstract: The pathophysiology of schizophrenia may involve perturbations of synaptic organization during development. The presence of cytoarchitectural abnormalities that may reflect such perturbations in the brains of patients with this disorder has been well-documented. Yet the mechanistic basis for these features of the disorder is still unknown. We hypothesized that altered regulation of the neuronal growth-associated protein GAP-43, a membrane phosphoprotein found at high levels in the developing brain, may play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(115 citation statements)
references
References 52 publications
11
102
2
Order By: Relevance
“…b-Tubulin has previously been used as internal control 52,53 and several studies have found expression of b-Tubulin to be unaffected in schizophrenic brain. 54,55 However, in order to further minimize the potential effect of dendritic loss on bTubulin expression, we used an antibody that recognizes not only the neuron-specific isoform III, but all b-Tubulin isoforms (I, II, III, IVa and IVb), representing both neuronal and non-neuronal tubulin expression. Examples of representative immunoblots are shown in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…b-Tubulin has previously been used as internal control 52,53 and several studies have found expression of b-Tubulin to be unaffected in schizophrenic brain. 54,55 However, in order to further minimize the potential effect of dendritic loss on bTubulin expression, we used an antibody that recognizes not only the neuron-specific isoform III, but all b-Tubulin isoforms (I, II, III, IVa and IVb), representing both neuronal and non-neuronal tubulin expression. Examples of representative immunoblots are shown in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…However, the distinctive features of such subjects constrains the extent to which findings from these studies can be generalized to other forms or earlier stages of the illness. Indeed, studies of elderly, chronically hospitalized subjects with schizophrenia have yielded some findings such as increased levels of synaptophysin protein in the prefrontal cortex (Gabriel et al 1997), that appear to be in the opposite direction to the decreased levels of this protein observed in studies of younger subjects with the disorder (Perrone-Bizzozero et al 1996;Glantz and Lewis 1997;Karson et al 1999). For most postmortem studies, especially of individuals in the early to mid-stages of a psychiatric disorder, who are most likely to die by suicide or by an accident or illness not apparently related to the primary disease process, such prospective, antemortem assessments are not possible.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…These abnormalities include increased neuronal cell packing density (Selemon et al, 1995), decreased expression of synaptophysin protein and mRNA (Perrone-Bizzozero et al, 1996;Eastwood et al, 2000), and decreased expression of RSG4 mRNA, a gene that regulates G-coupled intracellular signaling (Mirnics et al, 2001). All of these findings are consistent with reduced connectivity and diminished synaptic signaling in the visual cortex.…”
Section: Introductionmentioning
confidence: 99%